1982
DOI: 10.1002/bbpc.198200047
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐One‐Dimensional Behaviour of Hydrogen in H0.35MoO3 and H0.33WO3 as Revealed by Proton NMR

Abstract: The 1H NMR has been studied in the hydrogen bronzes H0.35MoO3 and H0.33WO3 prepared by galvanostatic cathodic reduction. Both systems reveal an extreme anisotropy of the hydrogen mobility due to quasi‐one‐dimensional behaviour. – In H0.35MoO3 the temperature dependent 1H wideline data give strong evidence that hydrogen is clustered in quasi‐one‐dimensional channels. Analysis of the temperature dependence of the second moment M2, the transverse relaxation time T2, and the spin‐lattice relaxation time T1 yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
17
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
16
17
0
Order By: Relevance
“…Except for LDA at x = 0.25, the O a -a position is energetically the most favorable site for H regardless of the exchange-correlation functional and the H content. This is consistent with experiments for x < 0.25 [16][17][18][19], where H resides along the zig-zag chains of the O a sites in the intrabilayer region.…”
Section: H Adsorption Energy In Bulk Moo3supporting
confidence: 91%
See 2 more Smart Citations
“…Except for LDA at x = 0.25, the O a -a position is energetically the most favorable site for H regardless of the exchange-correlation functional and the H content. This is consistent with experiments for x < 0.25 [16][17][18][19], where H resides along the zig-zag chains of the O a sites in the intrabilayer region.…”
Section: H Adsorption Energy In Bulk Moo3supporting
confidence: 91%
“…The most significant inconsistency regards the O site claimed to be the energetically most favorable for H to be adsorbed. Some studies [29,35,36] reported that the O a site is energetically more favorable than the other O sites, consistent with powder neutron diffraction [16,17] and nuclear magnetic resonance [18,19] for bulk H x MoO 3 with x ≤ 0.5. Other ab initio reports [23,24,26,28], in contrast, claimed that the O t site is more favorable than the O a site.…”
Section: Review On Previous Ab Initio Studiessupporting
confidence: 55%
See 1 more Smart Citation
“…The O2 sites (with an adsorption energy of 3.58 eV) are the most energetically favorable for hydrogen adsorption compared with the O1 (3.06 eV) and O3 (1.13 eV) sites (Supplementary Table 4). In addition, hydrogens are alternately located along the zig-zag chains of intralayer oxygen atoms ([001] direction) within MoO 6 octahedra 31 . By comparing the calculated thermodynamic stabilities for hydrogen diffusion along the [203] direction and along the [001] direction, we find the former to be slightly more energetically favorable (15 meV), possibly because of the cationic repulsion (Supplementary Fig.…”
Section: Analysis Of Intermediate States During Hydrogenationmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49] Sheik, Saleem and Aruldhas 50 observed very intense IR bands at 3215, 3185, 3172, and 3155 cm -1 in molybdenum hydrates. The position of the high-frequency band observed by these authors is in good agreement with the absorption at 3220 cm -1 detected in this experiment.…”
Section: R )mentioning
confidence: 99%